Uji Aktivitas Analgetik Ekstrak Biji Rambutan (Nephelium lappaceum L.) terhadap Mencit Putih Jantan - Fadilah, Nitya Nurul; Nofriyaldi, Ali; Fatwa, Elsa Nur (Health Information : Jurnal Penelitian, 2021)
Indonesia is rich in natural ingredients that have the potential as traditional medicinal plants, one of which is rambutan (Nephelium lappaceum L.) which is empirically efficacious as a pain treatment. The purpose of this study was to determine the analgesic activity of the ethanol extract of rambutan seeds and to determine the optimal dose of rambutan seed extract as an analgesic for white male mice. Rambutan seeds contain several main compounds such as flavonoids, tannins and saponins which are known to have analgesic activity. Rambutan extraction was carried out by maceration method using 70% ethanol, then phytochemical screening tests and extract drying shrinkage were carried out. Analgesic activity testing was carried out as many as 25 male white mice weighing 20-30 grams were divided into 5 groups. The treatment was carried out by administering the preparation between the negative control groups given 1% Na-CMC suspension. The positive control group or the comparison group were given paracetamol 1.3 mg/20 g BW of mice. The test dose group was given various doses of rambutan seed extract 37.5 mg, 75 mg, and 150 mg/20 g BW. Then observed stretching for 60 minutes, obtained the average stretch. The data obtained were analyzed by ANOVA test and LSD further test. The most effective dose is dose II 75 mg/20 g BW of mice. The results of this study are expected to prove that rambutan extract can empirically be useful as an alternative medicine for pain treatment.